Avaliação da tolerância ao calor de diferentes acessos de Jatropha curcas L. - Santos, Thaís Araujo dos (2016)
Jatropha curcasL. is a plant species whose seed produces a relatively simple oilto be converted into biofuel. The tolerance to high temperatures was analyzed in nine physic nut accessions grown in plastic pots in the experimental area of the Espírito Santo University, Brazil. The chlorophyll content and chlorophyll afluorescence induction kineticswere analyzed during the months of February and June/2015. It was observed in February (month with daily maximum temperatures around 35 °C), six of nine accessions had the highest chlorophyll levels. The OJIP curves of transient fluorescence of chlorophyll a demonstrated that three accessions had a inefficiency in the reoxidation capacity of quinoneAreduced, and two accessions showed a progressive reduction of plastoquinone accumulated; and one access presented damage in photosystem I, with incapacities in reducing the "pool" of plastoquinoneand plastocyanin in thylakoid membranes and P700+ chlorophyll a during the summer. In July, month with the highest changes on day/nighttemperature (30 / 19ºC), one access presented inativation of the oxygen evolution complex, two presented disconnection between the units of photosystem II; and three presented damage in the photosystem II, donor side, at the plastoquinone pool. Among the nine accessions, only one showed no inactivation of one or moresteps of the transient curve OJIP chlorophyll fluorescence during the periods analyzed. The principal component analysis applied to JIP Test data showed the formation of two groups representing the data collection period indicating the changes to distinguish the behavior of these plants in February and June have occurred since the initial reactions in Photosystem II to the end of the electron transport of photochemical stage when the final electron acceptors of photosystem I is reduced. The normalization of the data obtained by the JIP test showed the performance index of PSII (PIABS) as the main parameter to identify the tolerance levels to the hightemperature combined to other environmental stresses. This parameter is a multiparameter expression that combines some partial responses of the photosynthetic apparatus, including the three key properties that determine the potential activity of Photosystem II: the density of active reaction centers, the efficiency of photochemical reactions and the ability to transfer the electron excited after reducing the Quinone A. Thus, it was possible to classify the nine physic nut accessions in relation to the tolerance for high temperature conditions: NEF10,19,21> NEF13,15,16 <NEF12,14,17.Considering the results presented it was possible to verify that the access analysed have differences in the mechanisms to deal with stress associated with the ability to maintain the photochemical process balance combined with daily temperature variations. At the same time, we agree that is needed further investigation of the physiological differences in the photosynthetic apparatus of Jatropha curcas.